Beyond anxiety ebook Curiosity, creativity, and finding your life's purpose. - Beck, Martha (2025)
INSTANT NEW YORK TIMES BESTSELLER INDIE BESTSELLER USA TODAY BESTSELLER From bestselling author Martha Beck, a new path to overcoming anxiety by awakening the creativity within We live in an epidemic of anxiety. Most of us assume that the key to overcoming it is to think our way out. And for a while it works. But there is always something that sends us back into the anxious spiral we’ve been trying to climb out of. In Beyond Anxiety , Dr. Martha Beck explains why anxiety is skyrocketing around you, and likely within you. She also tells you how to not only reduce your anxiety but use it to propel you into a life filled with peace, meaning, and joy. Using a combination of the latest neuroscience as well as her background in sociology and coaching, Beck explains how our brains tend to get stuck in an “anxiety spiral,” a feedback system that can increase anxiety indefinitely. To climb out, we must engage different parts of our nervous system—the parts involved in creativity. Beck provides instructions for engaging the “creativity spiral,” in a process that not only shuts down anxiety but leads to innovative problem solving, a sense of meaning and purpose, and joyful, intimate connection with others—and with the world. The opposite of anxiety, it turns out, is a wonderful new way of life—one that can calm and inspire us as individuals and help us become a source of healing for everything around us.